2010
DOI: 10.1002/ajh.21593
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytosis is a risk factor for recurrent arterial thrombosis in young patients with polycythemia vera and essential thrombocythemia

Abstract: There is evidence that leukocytosis is associated with an increased risk of first thrombosis in patients with polycythemia vera (PV) and essential thrombocythemia (ET). Whether it is a risk factor for recurrent thrombosis too is currently unknown. In the frame of a multicenter retrospective cohort study, we recruited 253 patients with PV (n = 133) or ET (n = 120), who were selected on the basis of a first arterial (70%) or venous major thrombosis (27.6%) or both (2.4%), and who were not receiving cytoreduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Recently, also the presence of JAK2V617F mutation [6][7][8] and baseline leukocyte (WBC) count have been considered as disease-related cardiovascular risk factors of ET patients. This latter has been found to play a biological role in determining thrombosis, mainly acute coronary syndromes, in CMPN and particularly in ET, although it is presently not completely defined whether elevated WBC levels actually contribute directly to causing thrombosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, also the presence of JAK2V617F mutation [6][7][8] and baseline leukocyte (WBC) count have been considered as disease-related cardiovascular risk factors of ET patients. This latter has been found to play a biological role in determining thrombosis, mainly acute coronary syndromes, in CMPN and particularly in ET, although it is presently not completely defined whether elevated WBC levels actually contribute directly to causing thrombosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, leukocytosis-associated low platelet P2Y 12 function could result in a hemorrhagic tendency. In apparent contradiction, patients with high WBC counts have been reported to be more susceptible to thrombosis than bleeding [30,31,32]. P2Y 12 -independent mechanisms may account for the hypercoagulable state which has been reported to be associated with high WBC counts.…”
Section: Discussionmentioning
confidence: 68%
“…The WBC count was found to be an independent risk factor for thrombosis in MPN patients [29,30,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…The previous two cases were characterized by increased leukocyte and hematocrit counts, whereas the case described here was characterized by elevated leukocyte counts and platelet levels. It is reported that a JAK2 V617 mutation affects the number and activation of WBCs (17). Landolfi reported that the risk of thrombosis was significantly increased when the WBC count was >10x10 9 /l in patients with PV (13), although the underlying mechanism of thrombosis remains to be fully elucidated (18).…”
Section: Discussionmentioning
confidence: 99%